Effectiveness of a role-modeling intervention on student nurse simulation competency - Aronson, Barbara; Glynn, Barbara; Squires, Timothy (Clinical Simulation in Nursing, 2013)
Novice nurses are often inadequately prepared to respond to complex, patient care situations where patients' conditions deteriorate. Exposure to a video-taped intervention that role-models and reinforces expected behavior of an expert nurse before participation in a simulation may improve student nurse performance in a cost-effective manner. The primary purpose of this quasi-experimental pre-test, post-test study was to assess the preliminary effectiveness of a theory based role-modeling intervention on enhancing student nurse competency in responding to a simulated response to rescue event. Performance was measured by a previously validated Heart Failure Simulation Competency Evaluation Tool (c) (HFSCET). Total mean scores on the HFSCET for the pre-test (59.08) and post-test (87.08) were significantly different (p = .000); students performed better on the post-test after exposure to the role-modeling intervention. A power analysis indicated a large effect size (effect size = .926; alpha = 0.50; power = 0.991). Students who had a greater number of days between the intervention and the post-test had a lower score. This innovative intervention based on established learning theory may change the way educators prepare novice students to achieve expected clinical competencies in graded simulation performance assessments. (c) 2013 International Nursing Association for Clinical Simulation and Learning. Published by Elsevier Inc. All rights reserved.
17 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/003-811-864-193-208 tex.type: [object Object]
Keywords: Intervention; Nursing students; Performance assessment; Simulation; dept.nur

Competency assessment in simulated response to rescue events - Aronson, Barbara; Glynn, Barbara; Squires, Timothy (Clinical Simulation in Nursing, 2012)
Background: Reliable and valid instruments are needed to assess patient safety competencies, specifically nursing students' ability to appropriately respond to simulated rescue events. Methods: This was an instrument development study conducted with 152 senior nursing students in 2 phases. Results: Student groups performed poorly during the simulation scenario, with mean scores on the Heart Failure Simulation Competency Evaluation Tool ranging from 46% to 56%. Interrater reliability increased to .839 after item revision during Phase 2 of the study. Discussion: This simulation competency assessment package is ready to be tested with more diverse student groups and novice nurses in the practice setting. © 2012 International Nursing Association for Clinical Simulation and Learning.
7 citations (Crossref) [2023-10-31] Citation Key Alias: pop00146 tex.type: [object Object]
Keywords: Failure to rescue; Instrument development; Nursing students; Patient safety; Simulation; dept.nur

Evaluation of the McMahon Competence Assessment Instrument for use with midwifery students during a simulated shoulder dystocia - McMahon, Erin; Jevitt, Cecilia; Aronson, Barbara (Journal of Midwifery & Women's Health, 2018)
IntroductionIntrapartum emergencies occur infrequently but require a prompt and competent response from the midwife to prevent morbidity and mortality of the woman, fetus, and newborn. Simulation provides the opportunity for student midwives to develop competence in a safe environment. The purpose of this study was to determine the inter-rater reliability of the McMahon Competence Assessment Instrument (MCAI) for use with student midwives during a simulated shoulder dystocia scenario. MethodsA pilot study using a nonprobability convenience sample was used to evaluate the MCAI. Content validity indices were calculated for the individual items and the overall instrument using data from a panel of expert reviewers. Fourteen student midwives consented to be video recorded while participating in a simulated shoulder dystocia scenario. Three faculty raters used the MCAI to evaluate the student performance. These quantitative data were used to determine the inter-rater reliability of the MCAI. ResultsThe intraclass correlation coefficient (ICC) was used to assess the inter-rater reliability of MCAI scores between 2 or more raters. The ICC was 0.86 (95% confidence interval, 0.60-0.96). Fleiss's kappa was calculated to determine the inter-rater reliability for individual items. Twenty-three of the 42 items corresponded to excellent strength of agreement. DiscussionThis study demonstrates a method to determine the inter-rater reliability of a competence assessment instrument to be used with student midwives. Data produced by this study were used to revise and improve the instrument. Additional research will further document the inter-rater reliability and can be used to determine changes in student competence. Valid and reliable methods of assessment will encourage the use of simulation to efficiently develop the competence of student midwives.
1 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000428796300010 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Article; Clinical Competence; Dystocia; Education; Nursing; Educational Measurement; Female; Humans; Infant; Newborn; McMahon Competence Assessment Instrument; Midwifery; Nurse Midwives; Observer Variation; Pilot Projects; Pregnancy; Reproducibility of Results; Shoulder; Simulation Training; Video Recording; assessment; clinical competence; competence; content validity; controlled study; correlation coefficient; dept.nur; dystocia; education; evaluation; expert system; female; human; instrument; intrarater reliability; midwife; midwifery education; midwifery student; newborn; nurse midwife; nursing education; observer variation; obstetric procedure; peer-reviewed; pilot study; pregnancy; priority journal; procedures; quantitative analysis; quantitative study; reliability; reproducibility; scoring system; shoulder; shoulder dystocia; simulation; simulation training; standards; teacher; validation study; validity; videorecording

Technology use and technological self-efficacy among undergraduate nursing faculty - Roney, Linda N.; Westrick, Susan J.; Acri, Mary C.; Aronson, Barbara S.; Rebeschi, Lisa M. (Nursing Education Perspectives (Wolters Kluwer Health), 2017)
AIM This study explored faculty responses to a survey about using technology to teach undergraduate nursing students. BACKGROUND Little is known regarding faculty confidence, technology use, or supports for integrating technology into nursing education. METHOD A descriptive correlational design was utilized to explore the relationship between technology use and technological self-efficacy in faculty (N = 272) who teach at Commission on Collegiate Nursing Education–accredited nursing programs. Instruments used were a sociodemographic questionnaire, the Roney Technology Use Scale, and the Technology Self-Efficacy Scale. RESULTS Participants who taught didactic content had moderate technology use as compared to those teaching didactic and clinical/laboratory who reported high levels of technology use. A weak relationship between age and technological self-efficacy (ρ =.127, p < .05) was also found. CONLUSION This research was an initial step in understanding levels of technology use and responses to this challenge by undergraduate nursing faculty.
10 citations (Crossref) [2023-10-31] Citation Key Alias: roneyTechnologyUseTechnological2017a
Keywords: Adult; Bivariate Statistics; Coefficient Alpha; Computer Assisted Instruction; Computer Literacy; Confidence; Confidence Intervals; Content Validity; Correlational Studies; Data Analysis Software; Descriptive Research; Descriptive Statistics; Education Research; Education; Nursing; Baccalaureate; Educational Status; Educational Technology – Utilization; Faculty Development; Faculty Practice; Faculty; Nursing; Female; Human; Male; Middle Age; Nonexperimental Studies; Nurse Faculty; Nursing Education; P-Value; Promotion and Tenure; Questionnaires; Scales; Schools; Nursing; Self-Efficacy; Socioeconomic Factors; Students; Nursing; Baccalaureate; Summated Rating Scaling; Surveys; T-Tests; Teaching Methods; Technological Self-Efficacy; Technology; adult; age; article; clinical laboratory; controlled study; dept.nur; dept.swk; female; human; human experiment; major clinical study; male; nursing education; nursing student; peer-reviewed; questionnaire; self concept; teaching

After the gap analysis: Education and practice changes to prepare nurses of the future - Beauvais, Audrey Marie; Kazer, Meredith Wallace; Aronson, Barbara; Conlon, Suzanne E.; Forte, Pamela; Fries, Kathleen S.; Hahn, Judith M.; Hullstrung, Russell; Levvis, Meg; McCauley, Paula; Morgan, Patricia Padula; Perfetto, Linda; et al. (Nursing Education Perspectives, 2017)
AIM The purpose of the study was to describe the Connecticut Nursing Collaborative-Action Coalition’s work in identifying and addressing gaps between nursing education and practice based on the Institute of Medicine’s Future of Nursing report. BACKGROUND Massachusetts Nurse of the Future (NOF) Competencies highlight the knowledge, skills, and attitudes/behaviors required for professional nurses. Integrating these concepts into the educational system will prepare the nursing workforce to respond to current/future health care needs and population health issues. METHOD Education and practice partners in four regions conducted a gap analysis of the education to practice transition for new graduate nurses using NOF as a framework for assessment. RESULTS Gaps in competencies were similar across regions. However, each organization uniquely addressed curricular gaps to best prepare nurses of the future. CONCLUSION Curriculum improvements will provide students the advantage of being prepared for the rapid changes happening in health care. Copyright © 2017 National League for Nursing
4 citations (Crossref) [2023-10-31]
Keywords: Academic-Practice Partnership; Connecticut; Curriculum; Education; Nursing; Forecasting; Future of Nursing Competencies; Gap Analysis; Humans; Massachusetts; New Graduate Nurses; Nursing Curriculum; Nursing Education; Nursing Staff; article; curriculum; dept.nur; forecasting; health care need; human; human experiment; nursing education; nursing staff; peer-reviewed; population health; skill; student; workforce